(untitled) (Research Nepal Journal of Development Studies, 2022)
Buddhism was first invented in Kapilvastu, Nepal. Vietnam war is considered the second most devastating war of the 20th century after the second world war. At the same time, Vietnam had always boasted of 2000 years of Buddhist history. The US-Vietnam war, which surpassed the records of the French-Vietnamese War finally ended after long negotiations in Paris and the total withdrawal of the US troops in 1975. In the intermittent period, the Buddhists engaged in non-violent demonstrations against war, which was brutally suppressed then. But it made a long-lasting impact, ultimately resulting in negotiations and the end of the war. Buddhism played a significant role in ending the Vietnam War. Thus the main objective of the study is to analyze and review the roles of Buddhism to end the war. This study is based on available literature on the subject. Thus it is an in-depth literature review of referenced texts and literature. It is also a content analysis of selected literature. The Harris and pentagon analysis have mentioned little but the role of Buddhism, the monks, the unity of Theravada and Mahayana sect, and the self-burn of a monk were the significant internal factors to end the war to reestablish the peace.